Hubungan Pengetahuan Dan Persepsi Ibu Balita Tentang Pelayanan Kesehatan Balita Selama Pandemi Covid 19 Dengan Pelaksanaan Tele Konsultasi Pelayanan Kesehatan Balita Di Kabupaten Banyumas - Sumarni Sumarni; Fitria Prabandari (Universitas Muhammadiyah Surakarta, 2021)
Coronavirus is a contagious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV 2) virus. Health services for infants and toddlers during the Covid-19 period experienced many changes due to the risk of transmission to either infants or toddlers or health workers. Monitoring under five at risk, immunization services, vitamin A, is carried out by appointment / tele consultation / home visit. Health workers provide their telephone numbers or health facility numbers that can be contacted for tele consultations or appointments if the child requires further monitoring or services. This study aims to determine the relationship between knowledge and perceptions of mothers on the implementation of health services for children under five in Banyumas Regency. The research method uses quantitative methods. This type of research is observational with a cross sectional approach. The number of samples in this study were 30 mothers using simple random sampling technique. Data analysis using chi Square test. The results showed that there was a relationship between maternal knowledge and the implementation of telephoto counseling for toddler health services during the Covid-19 period (p = 0.000 α (0.05)) and there was a relationship between maternal perceptions and the implementation of telephoto counseling for toddler health services with the value at Pademic Covid-19 (p = 0.000 α (0.05)) The conclusion in this study is that there is a relationship between maternal knowledge and perceptions with the implementation of telephoto health service consultation for children under five during the Covid-19 pandemic.Keywords: Knowledge, Perception, Tele Consultation